2020
DOI: 10.1590/1678-4499.20200014
|View full text |Cite
|
Sign up to set email alerts
|

High rates of agricultural gypsum affect the arbuscular mycorrhiza fungal community and coffee yield

Abstract: High rates of agricultural gypsum, above the recommended levels, have been used on a regular basis to deepen plant roots and to alleviate recurrent water stress in Cerrado areas. However, very little is known about the consequences of this practice to arbuscular mycorrhizal fungi (AMF). Therefore, the objective of this study was to evaluate whether or not applying high rates of agricultural gypsum affects the mycorrhizal fungi community, glomalin content and coffee yield. The study rates were: 0; 3.5; 7.0; 14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
2
4
0
Order By: Relevance
“…In the four coffee-growing provinces of Peruvian San Martin State, 35 different morphospecies were detected in 12 coffee plantations, with 14-24 morphospecies recovered per province. The majority of previous studies with coffee report a similar AMF species richness (16-37 species) as found in our study [90][91][92][93][94][95][96], with some reporting higher species richness (43 and 79 species; [52,97]). The large variation in AMF species richness was often explained by the coffee production systems, with a generally higher AMF richness under the shadow (shade-green systems), as these systems allow the interaction of coffee with other plant species of the plantations through the belowground AMF network, as well as by different climatic conditions of the regions and the edaphic soil characteristics [93].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the four coffee-growing provinces of Peruvian San Martin State, 35 different morphospecies were detected in 12 coffee plantations, with 14-24 morphospecies recovered per province. The majority of previous studies with coffee report a similar AMF species richness (16-37 species) as found in our study [90][91][92][93][94][95][96], with some reporting higher species richness (43 and 79 species; [52,97]). The large variation in AMF species richness was often explained by the coffee production systems, with a generally higher AMF richness under the shadow (shade-green systems), as these systems allow the interaction of coffee with other plant species of the plantations through the belowground AMF network, as well as by different climatic conditions of the regions and the edaphic soil characteristics [93].…”
Section: Discussionsupporting
confidence: 87%
“…These genera are often the most prevalent in coffee plantations [91,94,98,99]. The genera Rhizoglomus, Sclerocystis, Entrophospora, Dominikia, Ambispora, Diversispora, Gigaspora and Sieverdingia have also been reported from coffee plantations worldwide [90,91,[93][94][95][96][97] but represent a lower species richness, as reflected in the current study.…”
Section: Discussionsupporting
confidence: 54%
“…Another study reported that applying AG at 7 Mg·ha −1 to soil used for coffee crops resulted in a greater diversity of mycorrhiza species. However, at a high rate of 56 t·ha −1 of AG, this diversity and mycorrhizal colonization of coffee roots was reduced (Cogo et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…In the surface layer of soil, negative correlations between MBC and arylsulphatase activity and between MBN and β‐glucosidase were observed. In soil under coffee crop, there was a linear decrease in extractable glomalin‐related soil protein to mycorrhizal fungi when increased the AG rate (Cogo et al, 2020). There is no doubt the value of AG used as an ameliorant in acid soils decreases aluminium saturation and increases S at deeper layers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation